Analyzing The Relationship Between Students’ Reading Interest and Comprehension of Descriptive Texts - Saptarina, Eva; Rizki Amelia, Kiki; Sartika, Dewi (English Education Study Program Faculty of Teacher Training and Education, 2023)
Developing interest in reading in students is essential to improving their reading comprehension. This study's objective was to look at the relationship between seventh-grade students at SMP Negeri 1 Kayuagung's reading interest and reading comprehension of decriptive text. The study utilized a quantitative correlational methodology, selecting forty students through purposive sampling from a population estimated to be 313 in size. Multiple-choice reading comprehension questions and a reading interest questionnaire were utilized to obtain the data. After confirming the normalcy and homogeneity of the data, Pearson's Product Moment Correlation was employed for analysis. With a significant r-value (0.808) higher than r-table (0.304) above the predetermined significance level, the results demonstrated a robust relationship between reading interest and reading comprehension. Simply put, students who were more engaged in reading were seemed inclined to have stronger reading comprehension, which aided their academic progress. Keywords: Reading interest, Reading comprehension, Descriptive texts